Synthesis, biological evaluation, molecular docking, and DFT calculation of novel 4-(1H-indol-3-yl)-3-methyl-1-phenyl-1H-furo[2,3-c]pyrazole derivatives - Mahmoud Nassiri; Jaber Salehzadeh; Sahar Mohajeri (Results in Chemistry)
A new series of 4-(1H-indol-3-yl)-3-methyl-1-phenyl-1H-furo[2,3-c]pyrazole derivatives were efficiently designed and prepared using a simple and novel route in excellent yields by multi-component reactions between 3-methyl-1-phenyl-2-pyrazolin-5-one, aryl glyoxals, and indoles. These reactions proceeded in acetone at reflux under catalyst-free conditions in the presence of triethylamine as a base for 2 h. The structure of all of the synthesized products was exhaustively established by NMR, IR, EI-MS, and elemental analyses. In addition, an extensive theoretical study was carried out such as density functional theory (DFT) calculation carried out at the B3LYP/6–311++G (d, p) level of theory, theoretical predictions of biological activities, and molecular docking. Compound 4g demonstrated IC50 values of 0.036 ± 0.002 μM and 0.046 ± 0.002 μM, respectively, against MCF-7 and A549 cell lines. Among the all studied compounds, the best docking results were related to 4g displayed. In fact, this compound had the most negative ΔGbind (−9.21 kcal/mol) that showed favorable interactions with the key amino acid residues at active site of EGFR receptor. The study successfully introduces a series of furo[2,3-c]pyrazole derivatives with promising biological activity, especially compound 4g, which shows significant anticancer potential. Its high affinity for the EGFR receptor highlights its importance in cancer treatments. This study lays the foundation for future research on advanced cancer treatments.